ANALISIS KAPASITAS BALOK DAN PELAT LANTAI PADA PROYEK GEDUNG PUSAT PEMBELAJARAN ARTNZ-GEISE TAHAP II PARAHYANGAN UNIVERSITAS PARAHYANGAN - BANDUNG - Indartono Rivai; Arwina Nursanti; Tri Rahmat Utama (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2020)
The design of the beams and floor slabs of a building is very important, Which is one of the building structures that functions as a load bearing and the forces acting on the beams and transmitting them to the column. Perencanaan balok dan pelat lantai suatu bangunan sangatlah penting, yang merupakan salah satu struktur bangunan yang berfungsi sebagai penahan beban dan gaya-gaya yang bekerja pada balok dan meneruskannya pada kolom. In the second phase of the ARTNZ GEISE Learning Center Building Project, Parahyangan University Bandung, the author wants to know how to analyze the capacity of beam and floor plates in a project, and how many results of beam and floor plate capacity are obtained in the analysis of these calculations. The research was started by studying the basic theory from the literature study. Collecting data and then modeling using the SAP 2000 program to analyze the structure under review. Analysis using SAP 2000 makes it easy to calculate the capacity of the structure, by defining the drawings, materials, and building loads into the system, you will immediately know the capacity of the structure. Based on the results of SAP 2000 analysis, different moment values are obtained in the beam. Likewise, the results of different analysis of floor plates are influenced by the area of the received load and the location of the floor plates. In this study also obtained differences in the calculation of SAP 2000 against the actual data in calculating the capacity of beams and floor plates.